Posture Deficits and Recovery After Unilateral Vestibular Loss: Early Rehabilitation and Degree of Hypofunction Matter - Lacour, Michel; Tardivet, Laurent; Thiry, Alain (Frontiers in Human Neuroscience, 2022)
Postural instability and balance impairment are disabling symptoms in patients with acute unilateral peripheral vestibular hypofunction (UVH). Vestibular rehabilitation (VR) is known to improve the vestibular compensation process, but 1) its effect on posture recovery still remains poorly understood, 2) little is known about when VR must be done, and 3) nobody knows whether the degree of vestibular loss matters. We analyzed posture under static (stable support) and dynamic (unstable support) conditions with eyes open: (EO), closed (EC), and optokinetic stimulation using non-linear analyses in two groups of UVH patients submitted to VR program (unidirectional rotatory paradigm) performed either early (first two weeks) or later (fifth to sixth week) after vertigo attack. Degree of vestibular loss was attested by the gain of the angular horizontal vestibulo-ocular reflex (aVOR) recorded on the hypofunction side before rehab. Four sub-groups of UVH patients were determined on the basis of both the stage of VR (early vs late) and degree of vestibular hypofunction (aVOR gain below 0.20 or above 0.20). All non-linear analyses parameters were significantly altered in the four sub-groups tested before VR compared to controls. In static posturography conditions, significantly greater instability, higher energy to control posture, larger sway without feedback corrections, and lower time of automatic control of posture were observed. After VR, all sub-groups recovered near normal postural performance with EO and EC, but still exhibited altered postural performance with optokinetic stimulation. In dynamic posturography conditions, the percentage of patients able to perform the postural tasks with EC and optokinetic stimulation was significantly higher in the sub-groups with aVOR gain > 0.20. After VR, improvement of the non-linear analyses parameters was in function of the stage of rehab and degree of vestibular hypofunction. In the dynamic task in which the vestibular input is more crucial for balance control (without vision on unstable support), a better recovery was found in patients with early VR and pre-rehab aVOR gain above 0.20. The data extend to dynamic balance recovery the critical period concept and the crucial role of the degree of vestibular hypofunction we already demonstrated for the vestibulo-ocular reflex recovery.